Some trends on artificial intelligence in legal education - González Aguilar, Hugo (2023)
The objective of this article is to analyze some trends regarding artificial intelligence in legal education. An analysis of Scopus research has been carried out from 2016 to 2024 based on the following categories: improves learning results, impact on legal education, disruptive changes, anomization of judicial documents, the use of AI in legal research, training students in legal databases, articulation of theory-practice, contrast between AI and traditional education, development of personalized learning, design of a virtual classroom, regulation of AI, implementation of AI in the curriculum and legal advice. It is concluded that AI improves student learning, affects the development of personalized learning, harmonizes theory with practice and generates innovative changes in the curriculum.